Rituximab for Remission Induction in a Patient with Relapsing Necrotizing Scleritis Associated with Limited Wegener's Granulomatosis - (:unkn) unknown (INFORMA HEALTHCARE, 2008)
Purpose: The authors report a case of necrotizing scleritis associated with Wegener's granulomatosis (WG), which was treated with rituximab for relapsing disease. Method: Observational case report. Results: A 32-year-old male patient presented with necrotizing scleritis in his left eye. The patient was diagnosed as having limited WG. Cyclophosphamide was begun. Under maintenance treatment with azathioprine two relapses of scleritis occurred. Since a high cumulative dose of cyclophosphamide (22.5 g) was utilized initially, two intravenous infusions of rituximab 1 g was given. Complete resolution of scleritis occurred. Conclusions: Rituximab may be effective to induce remission in patients with scleritis due to WG.
Keywords: Rituximab; systemic vasculitis; Wegener's granulomatosis; immunosuppression; necrotizing; scleritis; THERAPIES